If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8p + 7 = 7(1 + 8p) Reorder the terms: 7 + -8p = 7(1 + 8p) 7 + -8p = (1 * 7 + 8p * 7) 7 + -8p = (7 + 56p) Add '-7' to each side of the equation. 7 + -7 + -8p = 7 + -7 + 56p Combine like terms: 7 + -7 = 0 0 + -8p = 7 + -7 + 56p -8p = 7 + -7 + 56p Combine like terms: 7 + -7 = 0 -8p = 0 + 56p -8p = 56p Solving -8p = 56p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-56p' to each side of the equation. -8p + -56p = 56p + -56p Combine like terms: -8p + -56p = -64p -64p = 56p + -56p Combine like terms: 56p + -56p = 0 -64p = 0 Divide each side by '-64'. p = 0 Simplifying p = 0
| v+v+v+50=180 | | 18+-27= | | (6x)(1/6x3) | | F(x)=65(.64) | | 7-36/5=x | | 3(a-4b)-2(a+4b)= | | -5(-4+2x)=-10 | | 6-2u=-4 | | 3x+9y=32 | | 9x-9=-63 | | -8x+7x-9x-x= | | 20(v+3)-4v=4(4v+1)-10 | | 6x-1=-5x+10 | | -5(-4+2x)=10 | | C=mv-mu | | 20-4x=8-4(x-3) | | 11x-(5x-5)=47 | | 0.5x-1.3=-8.8 | | 3(4x-2)=10x+10 | | 4(5-x)+3=20 | | -5(1x+9)=-20 | | 2(p-4)=12 | | 6x+30=3x-3 | | 5(4a+2b)-3(2a+b)= | | 2x=180-80 | | -3.8T+4=4.4T-3 | | 6x+147=16x-13 | | 13a-8+4=11 | | 13a-81+4=11 | | 2x=180-76 | | 3(x+4)+8=5x+2 | | y=20x+34 |